1999
DOI: 10.1002/(sici)1097-461x(1999)72:3<177::aid-qua2>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

The polarizability and the second hyperpolarizability of tetrakis(phenylethynyl)ethene and several of its lithiated derivatives

Abstract: The polarizability ␣ and the second hyperpolarizability ␥ of Ž . Ž . tetrakis phenylethynyl ethene TPEE are compared and analyzed in connection with the Ž . properties ␣, ␥ of a series of selectedrdesigned molecules having different conjugation patterns. Several lithiated derivatives of TPEE are designed and shown to have very enhanced second hyperpolarizabilities; for example, one of the lithiated TPEE has a 1.6 = 10 3 times larger second hyperpolarizability than that of benzene. The potential of the proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…However, most of these compounds involve only a few representative elements and many remain poorly characterized, especially from a structural viewpoint. The element best studied is Hg(II), of which compounds with three to six metal atoms have been reported. Other members of this family of compounds include Sn(IV), ,, Li, ,, Mg, Al, , and Ge derivatives. , Many Hg(II) derivatives were prepared by metalation, but in a few cases transmetalation reactions using the corresponding Sn(IV) 1 or Li 3 derivatives were used. Most Sn(IV) compounds were synthesized by reacting NaSnMe 3 with the corresponding halobenzene, but 1,3,5-C 6 H 3 (SnMe 3 ) 3 has also been prepared from the corresponding Li derivative. , Lithium derivatives were obtained by reacting organolithium compounds with halobenzenes.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these compounds involve only a few representative elements and many remain poorly characterized, especially from a structural viewpoint. The element best studied is Hg(II), of which compounds with three to six metal atoms have been reported. Other members of this family of compounds include Sn(IV), ,, Li, ,, Mg, Al, , and Ge derivatives. , Many Hg(II) derivatives were prepared by metalation, but in a few cases transmetalation reactions using the corresponding Sn(IV) 1 or Li 3 derivatives were used. Most Sn(IV) compounds were synthesized by reacting NaSnMe 3 with the corresponding halobenzene, but 1,3,5-C 6 H 3 (SnMe 3 ) 3 has also been prepared from the corresponding Li derivative. , Lithium derivatives were obtained by reacting organolithium compounds with halobenzenes.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have shown that lithiation has a significant effect on the excitation spectrum of the compound and leads to a remarkable increase of the (hyper)polarizabilities. [43–48] For this purpose, the CIS/6‐31G* method has been used for the computation of the electronic spectrum of the clusters under study. The allowed transitions computed by the CIS method may be compared with standard one‐photon spectroscopic data and can be observed by single photon experiments such as UV.…”
Section: Resultsmentioning
confidence: 99%
“…A strategy to enhance hyperpolarizabilities of organic molecules with increasing acceptance is the substitution/doping by alkali metal atoms. Since early studies based on semiempirical methods , suggested that the replacement of hydrogen by lithium atoms in organic molecules could lead to extremely large second hyperpolarizabilities, this issue has been subject of several investigations. Correlated ab initio calculations reported by Raptis et al showed that the electronic second hyperpolarizability of hexalithiobenzene is around 3 orders of magnitude larger than the second hyperpolarizability of benzene.…”
Section: Introductionmentioning
confidence: 99%